The Impact of Institutional Pressures of Climate Change Concerns on Corporate Environmental Reporting Practices: A Descriptive Study of Malaysias Environmentally Sensitive Public Listed Companies - Jaaffar A.H.; Amran A.; Rajadurai J. (SAGE Publications Inc., 2023)
Malaysian companies have dramatically increased their corporate environmental reporting (CER) practices in response to institutional pressures related to concerns about climate change. Based on a content analysis of annual reports, sustainability reports, and websites of 209 Malaysian environmentally sensitive public listed companies (ESPLCs), we describe CER practices with respect to various environmental strategies implemented by companies over a 5-year period. The results show that environmental strategies include pursuing sequential progression from noncompliance to compliance, and beyond in response to external factors such as institutional pressures and climate change concerns. This progression is manifested by the extent and quality of CER practices as pursued by Malaysian ESPLCs. 2018, The Author(s) 2018.